Landslide deformation hysteresis regularity based on permeability of landslide and reservoir water change - Yiliang Liu; Xuan Tang; Fangdang Xu; Kun Song; Jianxiang Chen; Xin Xue; Chenxi Gao; Qinglin Yi (地质科技通报, 2022)
The deformation evolution of reservoir landslides of ten lags behind the variation in the reservoir water level during the operation of the Three Gorges Project, showing a deformation hysteresis effect, and the hysteresis effect is different with the difference in the permeability coefficient and fluctuation rate of reservoir water. Taking the Baijiabao landslide in the Three Gorges Reservoir area as an example, the variation law of the deformation lag time under different permeability coefficients k and reservoir water level decline rates v is studied by field investigation, monitoring data analysis and numerical simulation. The results show that when the permeability coefficient of the landslide is constant, the higher the decreasing rate of reservoir water level is, the more obvious the groundwater lag. When the reservoir water level drops at a certain rate, the greater the permeability coefficient of the sliding body is, the faster the groundwater drop.When the permeability coefficient of the sliding body is 0.85 m/d, the higher the rate of reservoir water level decline is, the shorter the deformation lag time of the landslide.The corresponding lag time is 3.74-9 d under different decline rates of the reservoir water level.When 0.47 < v/k < 1.18, 0.24 < relative deformation lag time < 1; when 1.18 < v/k < 2.38, 0 < relative deformation lag time < 0.24. When the reservoir water level decline rate is constant, the larger the landslide permeability coefficient is, the shorter the landslide deformation lag time is. Under different reservoir water level decline rates, the change rule of the relative deformation lag time with increasing v/k value is roughly the same, v=1.8 m/d, and the corresponding lag time of different permeability coefficients is 1.7-8 d. When 0.52 < v/k < 0.84, 0 < relative deformation lag time < 0.16; when 0.84 < v/k < 2.12, 0.16 < relative deformation lag time < 0.43; when 2.12 < v/k < 9, 0.43 < relative deformation lag time < 1. The research results have strong application value for the prediction and warning of reservoir landslides.